The Diversity of Endophytic Bacteria from the Traditional Medicinal Plants Leaves that Have Anti-Phytopathogens Activity - Syukria Ikhsan Zam; Anthoni Agustien; Syamsuardi Syamsuardi; Akmal Djamaan; Irfan Mustafa (Journal of Tropical Life Science, 2019)
Endophytic bacteria live in plant tissues which utilized in plant protection against phytopathogens. This study aims to investigate the diversity of endophytic bacteria from the leaves of traditional medicinal plants that has anti-phytopathogens properties. Isolation of endophytic bacteria was done by spread plate method. The bacteria were characterised by Gram staining and the 16S rRNA gene analysis. Further screening of anti-phytopathogen activity used disc diffusion method for Ralstonia solanacearum, Xanthomonas campestris, Fusarium oxysporum, and Sclerotium rolfsii. All togethers, sixteen isolates of endophytic bacteria from the leaves of eight medicinal plants species were obtained. Fourteen isolates had an anti-phytopathogen (with eight isolates against R. solanacearum, seven isolates against X. campestris, nine isolates against F. oxysporum, and five isolates against S. rolfsii). From the 14 isolates identified, phylum Firmicutes were dominant (64.3%), followed by Proteobacteria (28.6%), and Actinobacteria (7.1%). Phylum Firmicutes consists of Bacillus indicus (BJF1, TCF1, and MCF2), Bacillus pumilus (CAF4), Bacillus sp. (CAF1), Bacillus subtilis (AAF2, MCF1, CAF3, and MCF3); phylum Proteobacteria consists of Pantoea agglomerans (CAF2), Pantoea stewartii (AAF4), Pseudomonas oryzihabitans (AAF3), and Pseudomonas psychrotolerans (AAF1); and phylum Actinobacteria consists of Kocuria kristinae (CSF1).